Imagens extremas no cinema underground - Maschke, Guilherme Malo (Universidade do Vale do Rio dos Sinos, 2018)
The theme of this thesis is the extreme image in underground cinema. However, we shall not deal with the underground as a whole, for we are delimiting our corpus to the following movies: War Is Menstrual Envy (1992); A Bitter Message of Hopeless Grief (1988); Dead Man II: Return of the Dead Man (1994); The Loneliest Little Boy in the World (2000), and Extase de Chair Brisée (2005). We understand that our problem may be summarized with this question: how is the extreme present in underground cinema? Looking for an answer for this question, and pointing to which elements of this extreme image are lasting in these objects, we articulate our methodological proposal in three axes: escavation, as in Jusi Parikka (2012), to find the objects and information about them; Henri Bergson's (2006) intuitive method, seeking to outline the virtual and actual of the research; cartography as proposed by Suzana Kilpp (2015), and Massimo Canevacci (1997), forming two constellations where they the audiovisual aspects of our objects are analyzed. As a way to plunge theoretically in what we propose as extreme images, we approach the work of French theoretician, Georges Bataille (1929), and also of commentator authors such as Georges Didi-Huberman (2015), Benjamin Noys (2000), and Eliane Robert Moraes (2002). Our theoretical basis connected to audiovisual and cinema starts with the conception of audiovisual as a corporeal and visceral experience, as presented by Jusi Parikka (2012), Thomas Elsaesser (2010), Laura Wilson (2015), and Jack Sargeant (2015). For our final considerations, we are pointing towards a constitution of such extreme images in virtual disfiguration and beastlike potentials, which constitute, each one with its own particularities, an extreme image both in visual and audible aspects.
Keywords: Comunicação; Audiovisual; Georges Bataille; Cinema underground; Estética; Imagem; Communication; Audiovisual; Georges Bataille; Underground cinema; Aesthetics; Image; ACCNPQ::Ciências Sociais Aplicadas::Comunicação